2018
DOI: 10.1007/s00431-017-3085-7
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing normality following the diagnosis of a childhood chronic disease: does “rare” make a difference?

Abstract: Living with a childhood chronic disease can be challenging, especially if the diagnosis involves a rare condition. This study sought to elucidate how the diagnosis of a rare disease, as compared to a common, chronic condition, may influence maternal experiences of childhood illness. We conducted face-to-face, semi-structured interviews with 26 mothers of children treated in a pediatric hospital in the province of Lecco, Italy. Half of the participants had a child diagnosed with Bartter syndrome (BS), and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 28 publications
1
63
0
2
Order By: Relevance
“…Our study found that changes in the caregiver's perception of their family life was a common coping strategy to minimize the emotional impact of ZSD. This strategy, particularly redefining what the “normal” parenting experience means, has been reported in other rare pediatric diseases as well [7,28]. Identifying this cognitive change may be useful in the development of resources to help facilitate this change of mindset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that changes in the caregiver's perception of their family life was a common coping strategy to minimize the emotional impact of ZSD. This strategy, particularly redefining what the “normal” parenting experience means, has been reported in other rare pediatric diseases as well [7,28]. Identifying this cognitive change may be useful in the development of resources to help facilitate this change of mindset.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in chronic pediatric disease have highlighted the relationship between caregiver stress and patient outcomes (as reviewed in [5]). Recently, several studies have sought to identify the challenges and barriers faced by caregivers in the rare disease community [[6], [7], [8], [9], [10], [11]]. For ZSD caregivers, however, information on their emotional status in relation to disease impact, in addition to their management and coping strategies to deal with personal and familial emotional stress, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies underline that parents must assume the role of ‘expert’ (Brewer et al, 2008; Pelentsov et al, 2015), since the rarity of the disease can increase the likelihood that professionals are not specifically competent in the subject matter. The diagnosis represents a turning point that could enable families to start adjusting to their new normality (Germeni et al, 2018), but this moment often requires a long period of time. Furthermore, being parents of a child with a rare disease has been shown to have profound implications on the physical and psychological health of the parents, particularly among mothers, and to negatively influence one’s relationship with his/her partner (Pelentsov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, when this child is born with an obvious severe disability then the impact is essentially different to the impact of having a child without a disability. Women recounted that the moment the disability was diagnosed, and the way in which this diagnosis was given to families had a fundamental impact on how the family understood the medical aspects related to the disability and how they prepared to meet the future challenges related to the child’s complex health and care needs [ 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%